Nghiên cứu hệ số điều chỉnh biên dạng khuôn đùn cao su - Hưng, Trần Vĩnh; Cường, Nguyễn Văn; Quang, Châu Mạnh (Vietnam Journal of Chemistry, 2014)
This paper introduces a method to identify the correction coefficient for extrusion moulds by means of experimental planning. On the basis of theory and experience, the software “Calculating the profile correction coefficient of rubber extrusion moulds” is designed to identify the mould correction coefficient and correction profile. At the same time, through this method, the research team present the results of types of corrected rubber felt seal moulds on the coach B80HN.